Spatial variation in the perception of urban residential environmental, quality of life in Srinagar city (J &K) - Malik, Tanweer Ahmad; Shukla, Vandana; Bhat, Suhail Ahmad (International Journal of Social Sciences and Management, 2015)
The paper examined the sensitiveness among the sample wards of Srinagar city – quality of life, built up condition, perception of residents annoyed by various environmental pollution indicators. Environmental quality may be analyzed objectively based on facts & figures .it should also be viewed through the mental map of residents the way they perceive their environment. The way they experience it such an image of the environment is bound to be partial, distorted, & simplified one .the Z-score variate has been used to examine the level of literacy. The spatial variation in perceiving the quality of life & the way to perceive the environment is reliant on the primary source the reason for the variation among the sample wards is due to the poor environmental management & socio- economic conditions. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 250-262 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12825